Yabuuchi Kiyoshi: His Life, Works and Contributions to the Chinese History of Science and Technology - MaZilang, Isa (WILAYAH: The International Journal of East Asian Studies, 2014)
The abstract is not available. To access, please order the printed version or browse the electronic version of this article.